Impact of blood group in dengue: a study - Joshi, Anagha A.; Muneer, Fazeela; R., Gayathri B.; N., Divyashree B. (International Journal of Advances in Medicine, 2019)
Background: Dengue can result in high mortality. Several studies have shown an association of blood groups with the severity of dengue. In our study we attempt to associate the prevalence of blood groups with the known hematological prognosticators and thus derive its impact on the severity of dengue. We aim to study the patterns and prevalence of different ABO blood groups in dengue fever. Methods: A total of 100 serologically proven dengue cases over a month’s period in November 2016 were recruited for our study. Their relevant hematological data (obtained by automated haematology analyser and peripheral smears) and blood grouping results were recorded and analyzed. Results: The age range was 5 months to 65 years with a slight male predominance. Analysis of the blood group patterns showed prevalence of O group (42%) followed by A and B group (27% each). B group was more prevalent in children (34%) and females (31%) with dengue. The patients with B group showed increased derangement in hematological parameters namely higher number of cases with B group showed rise in haematocrit (59%), an increased number of cases with leucopenia (56%), higher proportion of cases with lymphocytosis (45%) and severe thrombocytopenia (74%) when compared to the other blood groups. Conclusions: Our study shows that blood groups can impact severity of dengue and that B group is a risk factor for severity hence, such individuals warrant close supervision especially in the presence of other risk factors.